Trace Elements and Risk of Immune-Mediated Skin Disease: A Systematic Review and Meta-analysis - Shao, Xinyi; Ou, Yi; Chen, Tingqiao; Deng, Binbin; Zhang, Jingbo; Chen, Jin (Nutrition reviews, 2025)
Evidence regarding the relationship between serum trace element levels and immune-mediated inflammatory skin diseases (IMSDs) is inconsistent. In this systematic review and meta-analysis we aimed to evaluate the association between selected serum trace element levels (zinc [Zn], copper [Cu], iron [Fe], selenium [Se], and calcium [Ca]) and IMSDs (psoriasis, vitiligo, atopic dermatitis [AD], alopecia areata [AA], hidradenitis suppurativa, and bullous diseases). We conducted a comprehensive search on the PubMed, EMBASE, Scopus, China National Knowledge Infrastructure, and Web of Science databases from the database inception date to May 2, 2024. Studies measuring serum, plasma, or whole-blood levels of Zn, Cu, Fe, Se, or Ca in patients with IMSD compared to those in healthy controls were included. This study followed the guidelines of the Meta-analysis of Observational Studies in Epidemiology and the Preferred Reporting Items for Systematic Review and Meta-analyses guidelines. Two authors (X.Y.S. and Y.O.) independently reviewed the titles and abstracts of the identified studies using a standardized collection form. The primary outcome was the standardized mean difference with a 95% CI in serum trace element levels (Zn, Cu, Fe, Se, and Ca) between patients with IMSDs and healthy controls. Overall, 113 studies involving 7014 patients with IMSD were included in the meta-analysis. Compared with those in the healthy control group, serum Zn levels decreased in patients with vitiligo, psoriasis, and AA; serum Cu levels increased in patients with psoriasis, AD, and AA; serum Se and Fe levels decreased in patients with psoriasis and AD. Serum trace element levels showed more significant changes in patients with IMSDs than in healthy controls. These findings suggest that alterations in trace element levels may be associated with the occurrence, development, and prognosis of IMSDs.